Predictors of Adherence Toward Specific Domains of Diabetic Self-Care Among Type-2 Diabetes Patients - Degefa, Girma (Clin Med Insights Endocrinol Diabetes, 2020)
BACKGROUND: Adequate knowledge, awareness, and adherence to diabetic self-care practices are vital tools to protect patients from risks of disease complications, developing comorbidity and mortality. Therefore, this study aimed to assess specific domains of diabetic self-care practice and associated factors among patients with type-2diabetes in Hawassa University Comprehensive Specialized Hospital, Sidama regional state. MATERIALS AND METHODS: A hospital-based cross-sectional study design was conducted on 217 patients with type 2 diabetes from January 01 to April 30, 2020. A structured questionnaire and the Summary of Diabetes Self-Care Activities (SDSCA) tool were used to collect relevant data through interviewer administration. Statistical analysis was done using SPSS version 23. RESULTS: A total of 207 patients with type-2 diabetes were participated in the study with a 95% response rate. Overall 47.8% (95%CI: 41.2-55) of patients adhered to diabetic self-care practice. Concerning the specific domain of self-care practice, 54.6%, 39.1%, 28%, and 65.2% of patients adhered to a healthy diet, physical exercise, self-monitoring blood glucose (SMBG), and diabetic foot care practices, respectively. Besides, all patients received at least 80% of the prescribed doses and frequency of anti-diabetic agents and 60.4% had good glycemic control. Receipt of advice from treating physicians and having no familial history of diabetes were significantly associated with adherence toward eating a healthy diet, diabetic foot care, and SMBG. While male sex was associated with adherence toward healthy diet management. Moreover, having glucometer, age, male sex, diabetes duration ⩾ 5 years, and anti-diabetic treatment modality were associated with adherence toward SMBG. CONCLUSION: This study indicates 52.2%, 72%, and 60.1% of diabetes patients did not adhere to diabetic self-care, SMBG, and physical exercise, respectively. Improving awareness and regular diabetic education is imperative to scale up patients’ adherence toward diabetic self-care practice.